2016
DOI: 10.1021/acs.energyfuels.6b01110
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Regeneration of Basic Aluminum Sulfate SO2-Rich Solution by Vacuum Desorption

Abstract: Basic aluminum sulfate (BAS) wet flue gas desulfurization (FGD) is a promising renewable process used to remove sulfur dioxide (SO2) from flue gas, in which the regeneration of BAS SO2-loaded solution is of great importance for the reuse of BAS solution. In this paper, a novel regeneration method by vacuum desorption was developed to achieve superior regeneration performance for a BAS-rich solution. The operating parameter effect on SO2 desorption performance was thoroughly investigated in a lab-scale reactor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…For instance, basic aluminum sulfate has been used to absorb SO 2 from ue gas, [9][10][11][12] which proves the high absorptive ability, and our team has carried out the mechanism research. 13 However, research has been rarely conducted on desorption of the basic aluminum sulfate desulphurization-regeneration solution, which is a key step in the renewable wet desulfuration process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, basic aluminum sulfate has been used to absorb SO 2 from ue gas, [9][10][11][12] which proves the high absorptive ability, and our team has carried out the mechanism research. 13 However, research has been rarely conducted on desorption of the basic aluminum sulfate desulphurization-regeneration solution, which is a key step in the renewable wet desulfuration process.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, research has been rarely conducted on desorption of the basic aluminum sulfate desulphurization-regeneration solution, which is a key step in the renewable wet desulfuration process. Thus far, water bath heating 14 assisted by mechanical agitation, 15 microwaves, 16 ultrasonic waves [17][18][19] or vacuum-pumping 20 has been applied for enhanced desorption, exhibiting some improvements. However, these methods are limited by nonuniform heating and long desorption time; moreover, the relevant research is still at the laboratory stage, which is hard to industrialize.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the limestone-gypsum method, basic aluminum sulfate (BAS) wet FGD technology has many advantages to remove SO 2 from ue gas, such as high desulfurization efficiency, circular utilization of the absorbent, rare fouling, low investment and energy consumption, etc. [4][5][6] During the desulfurization process, BAS as the effective absorbent reacts with SO 2 from ue gas to form the complex Al 2 (SO 4 ) 3 $Al 2 (SO 3 ) 3 , which could reversibly occur decomposition under the condition of heating due to its thermodynamic instability, and that would be further oxidized by oxygen in ue gas as the following reactions: 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Through practice, it environmentally indicated that the latter might be the most promising regenerative desulfurization process, whereby Al 2 (SO 4 ) 3 $Al 2 (SO 3 ) 3 is decomposed by heating or reducing pressure, regenerating BAS with the recovery of pure SO 2 used to produce sulfur or sulfuric acid. 7 In particular, faced with a serious shortage of sulfur sources in China, there are better application prospects for BAS-desorption regeneration process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation